2011
DOI: 10.2215/cjn.08070910
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Novel and Commonly-Used Indices of Insulin Sensitivity in African American Chronic Hemodialysis Patients

Abstract: SummaryBackground Insulin resistance (IR) is highly prevalent in chronic hemodialysis (CHD) patients and is associated with poor cardiovascular outcomes. Hyperinsulinemic euglycemic glucose clamp (HEGC) is the gold standard for measuring IR. The comparison of commonly-used indirect indices of IR to HEGC has not been adequately performed in this population. Furthermore, the validity of newly proposed adipokine-based IR indices has not been explored. Design, setting, participants, & measurementsThis is an observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 37 publications
6
67
0
1
Order By: Relevance
“…However, this method is expensive and not suitable for use in clinical practice. HOMA-IR, however, is easy to perform and validated as a valuable alternative of insulin sensitivity both in non-CKD patients (11,35), in CKD patients stages III and IV (36,37), and in HD patients (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method is expensive and not suitable for use in clinical practice. HOMA-IR, however, is easy to perform and validated as a valuable alternative of insulin sensitivity both in non-CKD patients (11,35), in CKD patients stages III and IV (36,37), and in HD patients (10).…”
Section: Discussionmentioning
confidence: 99%
“…Hung et al (10) have shown that leptin/adiponectin ratio (LAR) and homeostasis model assessment corrected for adiponectin (HOMA-AD) were the better correlates of glucose-disposal rate measured by hyperinsulinemic euglycemic glucose clamp in chronic HD patients. LAR has been recently proposed as a new atherogenic index, since it has been associated with cardiovascular events in PD (6).…”
Section: Introductionmentioning
confidence: 99%
“…The mean of M/I was 5.162.2 1003mg/kg per minute per 1 mU/L insulin. As many as 24.0% of the subjects were considered insulin-resistant (M,4.0 mg/kg per minute), 63.5% of the subjects were considered insulinintolerant (M=4.0-7.5 mg/kg per minute), and only 12.5% of the subjects were considered insulin-sensitive (M.7.5 mg/kg per minute) (20). Clinical and biochemical characteristics of included subjects are shown in Table 1 stratified by quartiles of M distribution.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…2010 (8). Glucose concentrations were measured by using the glucose oxidase method and insulin by double-antibody RIA, (Glucose Analyzer 2; Beckman Coulter, Brea, CA, and DA RIA; Millipore, St. Charles, MO, respectively).…”
Section: Methodsmentioning
confidence: 99%